Identification of nutritional composition and antioxidant activities of fruit peels as a potential source of nutraceuticals - Hussain, Tarique; Kalhoro, Dildar Hussain; Yin, Yulong (Frontiers in Nutrition, 2023)
This study aimed to determine the nutritional composition and antioxidant properties of twelve peels of different fruit varieties such as apples, pomegranate, guava, strawberry, grapes and citrus. The highest values of TPC, TFC, lycopene, ascorbic acid (total carotenoids & TAC), reducing sugars non-reducing sugars and total soluble proteins were reported in Grapes (Black seedless) 54501.00 ± 0.82 μM/g dry wt., Guava (Gola) 198.19 ± 0.46 Rutin equivalent dry wt., Strawberry (Candler) 7.23 ± 0.33 mg/g dry wt., Citrus (Mausami) 646.25 ± 0.96 ug/g dry wt., Apple (Kala kulu-Pak) 14.19 ± 0.38 mg/g dry wt. & 12.28 ± 0.39 μM/g dry wt., Strawberry (Candler) 25.13 ± 0.40 mg/g dry wt., Pomegranate (Badana) 9.80 ± 0.43 mg/g dry wt., Apple (Kala kullu-Irani) 30.08 ± 0.11 mg/g dry wt. and Guava (Gola) 638.18 ± 0.24 mg/g dry wt. compared with its opponent peels of fruits respectively. All twelve peels of the fruit verities had 20 amino acids and presented as dry matter basis %. The highest trend of Glutamic acid + Glutamine, Glycine and Aspartic acid + Asparagine were observed in Pomegranate (Badana) 1.20 DM basis %, Guava (Surhai and Gola) 1.09 & 1.09 DM basis %, Strawberry (Desi/local & Candler) 1.15 & 1.60 DM basis % in response to other fruit peels respectively. Regarding the mineral profile, the highest values of nitrogen (764.15 ± 0.86 mg/100g), phosphorus (53.90 ± 0.14 mg/100g), potassium (3443.84 ± 0.82 mg/100g), ferric (1.44 ± 0.00 mg/100g), magnesium (1.31 ± 0.00 mg/100g), and manganese (0.21 ± 0.00 mg/100g) were found in Pomegranate (Badana), Grapes (Black seedless), Apple (Kala kulu-Pak) and Pomegranate (Badana) respectively in context to other fruit peels extract. Principal Component Analysis (PCA) and Significantly, high levels of variation were noticed among different variable of peels of fruit. Fruit variety and its peels have been distinctive variables in selecting genotypes. The dendrogram was distributed into two groups and consisted of eight varieties in the same group and four fruit varieties were in second group. Overall, results conclude that fruit peels have abundant antioxidants and some minerals which can effectively be utilized for nutraceuticals.